Sosialisasi Penyakit Mulut dan Kuku (PMK) pada Peternak di Desa Tutukey Kecamatan Pulau Leti Kabupaten Maluku Barat Daya - Arnold Ismael Kewilaa; Louisa Sarah Kamanasa; Amelia Engli Rumabatu; Karolina Seska Gisberthus; Dominggas E .L. Heriola; Tabita Mirulewan; Dalenia Payara; Natalia Ailerpitu; Yandre T. Samadara; Ningsih Teterma Mose; Sarah Tersia Sarak; Novalina Malwewan; Yohana R Leunupun; Marselina Hematang; Susanti Blessintya Tetrapoik (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The purpose of this activity is to socialize foot and mouth disease (FMD) to livestock breeders in Tutukey Village, Pulau Leti District, Southwest Maluku Regency. This activity was carried out in Tutukey Village, Pulau Letti District, Southwest Maluku Regency which took place in August 2025. The target of this activity was cattle breeders in Tutukey Village. The implementation of this activity includes 2 stages, namely: preparation and implementation. The implementation of the activity began with an approach to village officials and livestock communities in Tutukey Village by KKN students from the Off-Campus Study Program (PSDKU) of Pattimura University, Southwest Maluku Regency, Batch LII Wave I. Then a short interview was conducted to identify problems in the livestock sector. Based on the approach and problem identification, several problems were found related to cattle deaths caused by disease, lack of feed and clean water availability. In addition, the community was also shocked by information about the spread of foot and mouth disease on the island of Java, so this issue needed to be raised in a scientific discussion space through socialization activities. Based on these activities, the following conclusions can be drawn: Increased information, knowledge, and understanding of the causes, characteristics, spread, impacts, and prevention of FMD, and increased motivation among livestock farmers to develop their cattle farming businesses.